2011
DOI: 10.1002/adem.201180041
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Electropsun Poly(propylene carbonate) Ultrathin Fibers as Tissue Engineering Scaffolds

Abstract: Electrospinning is a desired method to produce ultrathin fibers for tissue engineering. In order to mimic the nanofibrous structure of the extracellular matrix (ECM) poly(propylene carbonate) ultrathin fibers were electrospun using N,N‐dimethyl acetamide as solvent. Cationic surfactant, cetyl trimethyl ammonium bromide, was found to aid in the formation of beadless fibers of poly(propylene carbonate). Electrospinning parameters viz. concentration of polymer and that of the surfactant used as an additive, flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The medium was subsequently removed and the precipitated formazan was dissolved in dimethylsulfoxide (150 mL well –1 ). The optical density of the solution was read using a microplate reader (ELx808, Biotek®) at a wavelength of 570 nm …”
Section: Methodsmentioning
confidence: 99%
“…The medium was subsequently removed and the precipitated formazan was dissolved in dimethylsulfoxide (150 mL well –1 ). The optical density of the solution was read using a microplate reader (ELx808, Biotek®) at a wavelength of 570 nm …”
Section: Methodsmentioning
confidence: 99%
“…433 Three-dimensional poly( propylene carbonate) architectures were prepared via electrospinning, which readily allows the production of interconnected flexible nanofibrous structures. 432 These electrospun poly( propylene carbonate) structures displayed slightly lower thermal stability and slightly enhanced mechanical properties compared to conventional poly( propylene carbonate) ( Table 12, compare entry 2a to 1b). Additionally, cell adhesion experiments indicated proper biocompatibility of the three-dimensional poly( propylene carbonate) structures, as the cells were seen to grow, migrate and differentiate.…”
Section: Polycarbonates In Biomedical and Pharmaceutical Applicationsmentioning
confidence: 99%
“…Park et al [132] used sol-gel electrospinning to prepare pure PPC nanofibers, and found that the mechanical properties of pure PPC were significantly improved after the heat treatment at 60 • C due to the highly bonded structure of nanofibers, which was further interpreted by SEM diagram. Nagiah et al [133] obtained PPC ultrathin fibers with 10% w/v polymer solution, which have good thermal stability, mechanical properties and high porosity.…”
Section: Degradable Electrospun Packaging Membranementioning
confidence: 99%